1978
DOI: 10.1007/bf00607447
|View full text |Cite
|
Sign up to set email alerts
|

Antipyrine disposition and liver size in the elderly

Abstract: This study has examined the contribution of decrease in liver size to the decline in drug metabolising capacity which occurs with ageing. Liver volume and antipyrine kinetics were measured in two groups of healthy individuals aged 20 to 29 years and 75 to 86 years and in a group of hospitalised patients aged 70 to 89 years. Liver volume was reduced in both groups of elderly people compared to the young group. Antipyrine plasma half-life was prolonged and antipyrine clearance was reduced in the group of elderly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
23
1
2

Year Published

1981
1981
2012
2012

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 88 publications
(28 citation statements)
references
References 19 publications
2
23
1
2
Order By: Relevance
“…Although serum creatinine did not correlate with serum GA or SUA in these patients, there is a well-defined fall in creatinine clearance with age that is not re flected by serum creatinine [Kampmann and Molholm, 1979], Cuny et al [1979] reported prolongation of SA elimination half times in the elderly, which suggests that enhanced rate of production of salicylate metabolites is not likely. Although age-related changes in drug distribution can significantly affect their se rum concentration [Klotz et al, 1975;Swift et al, 1978], we presently have no evidence that this mechanism can explain our observa tions.…”
Section: Discussioncontrasting
confidence: 40%
“…Although serum creatinine did not correlate with serum GA or SUA in these patients, there is a well-defined fall in creatinine clearance with age that is not re flected by serum creatinine [Kampmann and Molholm, 1979], Cuny et al [1979] reported prolongation of SA elimination half times in the elderly, which suggests that enhanced rate of production of salicylate metabolites is not likely. Although age-related changes in drug distribution can significantly affect their se rum concentration [Klotz et al, 1975;Swift et al, 1978], we presently have no evidence that this mechanism can explain our observa tions.…”
Section: Discussioncontrasting
confidence: 40%
“…Frequently the elderly are institutionalized, often with multiple pathologies, while the controls are in independent and community living. Swift et al (1978) have shown that metabolic rates can be significantly dependent on such environmental differences. Even when differences in lifestyle and pathology are minimized, a multitude of environmental and genetic factors such as smoking, drinking, Cusack etal.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have shown significant reductions in the clearance of many drugs metabolized by phase-1 pathways in the liver [78,79]. The main factor is probably represented by the age-related changes in liver size and hepatic blood flow as the activity of drug metabolizing enzymes is preserved [80].…”
Section: Drug Clearancementioning
confidence: 99%